Efeito da terapia periodontal não cirúrgica em fumantes e nunca fumantes - Ardais, Rodrigo (2012)
Smoking is a risk factor for periodontitis. Its effect over the immunologic and inflammatory systems may interfere with the healing response after periodontal therapy. To evaluate this effect, bleeding on probing is a fundamental clinical variable. The aim of this controlled clinical trial was to compare the effect of non surgical periodontal therapy on bleeding on probing in smokers and never-smokers. Thirty patients (15 per group) with untreated chronic periodontitis were recruited. The examinations occurred before and 3 months after non surgical therapy. Dichotomic (BOP total) and graded (BOP1 and BOP2) bleeding on probing exam were performed. Others variables of interest were visible plaque (VPI), marginal bleeding (MBI), probing depth (PD), clinical attachment level (CAL) and suppuration on probing (PS). The primary outcome was analyzed by differences on SS total. Twenty-five patients (14 never-smokers and 11 smokers) concluded the study. Groups’ differences were observed on VPI and MBI (p< 0.05). Alterations on PD, CAL and PS were not different between groups (p> 0.05). Therapy caused a reduction on BOP total in smokers and never-smokers, however, the difference was not statistically significant (p> 0.05). Greatest reductions on BOP2 in moderate probing depth sites (4-6 mm) and on BOP total in deep sites (≥ 7mm) were observed in never-smokers (p< 0.05). Smoking seems to have an effect on response to non surgical periodontal therapy, evaluated by bleeding on probing in moderates and deep sites.